Exploring the nutritional and functional potential of forage-based diets in poultry feeding systems: a systematic review toward sustainable avian nutrition - Amalyadi, Rezki; Karni, Ine; Aminurrahman, Aminurrahman; Nano Septian, I Gede; Al Gifari, Zaid (Environmental and Agriculture Management, 2025)
The rising demand for sustainable and welfare-conscious poultry production has driven renewed interest in forage-based feeding systems. This systematic review explores the nutritional and functional roles of various forage types such as legumes, grasses, and aquatic plants in poultry diets. The review synthesizes evidence from recent Scopus-indexed publications, focusing on nutrient composition, bioactive properties, performance outcomes, and potential limitations. Forages provide protein, essential fatty acids, antioxidants, and phytochemicals that can enhance feed efficiency, immunity, gut health, and product quality in poultry. Their integration also aligns with circular agriculture principles and improves animal welfare through behavioral enrichment. However, the practical adoption of forage in poultry systems is constrained by variability in nutritional value, the presence of anti-nutritional factors (ANFs), low digestibility, and seasonal availability. Strategies such as fermentation, enzyme supplementation, and preservation techniques offer promising solutions to these challenges. This review identifies key research gaps, including the need for standardization of forage nutritional profiles, optimal inclusion rates, and long-term health impacts. Future directions highlight the potential of integrating precision nutrition technologies and policy support to enhance forage-based systems. Overall, forage represents a valuable component of sustainable poultry feeding strategies that balance performance, welfare, and environmental stewardship.